The account of the statistical, given for correction programs of search defuses of radioelectronic means (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2009)
The description of algorithm and results of development of the software package for accumulation and use of the empirical information is given, with the purpose of increase of efficiency of diagnosing of radioelectronic means.